Resonance contribution to electron-impact excitation rate coefficients of helium-like S14+ ions. Issue 13 (January 2020) - Wu, Z W; Ren, C; Jiang, J; Xie, L Y; Zhang, D H; Dong, C Z
Synopsis: Electron-impact excitation rate coefficients of S 14+ ions have been studied by using a relativistic flexible atomic code that can account systematically for configuration interactions. Moreover, we also considered the resonance excitation contributions to the rate coefficients. It is found that the contributions of resonance excitation on rate coefficients is very important.